Affordable electricity supply via contracts for difference for renewable energy - Nils May; Karsten Neuhoff; Jörn C. Richstein (DIW Weekly Report, 2018)
The cost of renewable energy technology has plunged in recent years. But the extent to which electricity consumers can benefit from the reduced costs depends on the design of renewable remuneration mechanisms. Calculations of a financing model show that the current sliding premium is leading to increasingly higher risks for investments and in turn, increasing equity requirements. As a result, financing costs increase, which counteracts the lower cost of technology. Furthermore, increased equity requirements could negatively affect the diversity of players investing in renewable energy and thus the level of competition as well as the rate of project realization in the sector. A change towards contracts for difference (CFDs) can remedy the situation. CFDs lead to low financing costs and therefore reduce overall costs of supplying renewable electricity, reducing expected annual costs for German consumers by approximately 0.8 billion euros per year by 2030. They also safeguard consumers against high payments for renewable electricity in case of high electricity prices. A transition to CFDs provides the opportunity to create more effective and simpler incentives for system-compatible site selection and plant design.
Keywords: Q42; Q55; O38; 330; financing costs; contracts for difference; renewable energy policies; feed-in premium